2013
DOI: 10.1016/j.bandl.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

First and second language in the brain: Neuronal correlates of language processing and spelling strategies

Abstract: This study explores oscillatory brain activity by means of event-related synchronization and desynchronization (%ERS/ERD) of EEG activity during the use of phonological and orthographic-morphological spelling strategies in L2 (English) and L1 (German) in native German speaking children. EEG was recorded while 33 children worked on a task requiring either phonological or orthographic-morphological spelling strategies. L2 processing elicited more theta %ERS than L1 processing (particularly at bilateral frontal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Conversely, some studies reported that the skills underlying L1 and L2 spelling differ over time (Jongejan et al, 2007), where at least part of the differences may be related to the characteristics of the L1 writing system (Martin, 2017). Importantly, studies of brain dynamics have shown varying patterns of EEG activity as a function of population type (i.e., L1 vs. L2), especially during the spelling of words that require non-phonological strategies (Weber et al, 2013). In this study, we compared children with (L1) and without (L2) exposure to Catalan, the language of instruction, outside school.…”
Section: Spelling Development In a Second Languagementioning
confidence: 99%
“…Conversely, some studies reported that the skills underlying L1 and L2 spelling differ over time (Jongejan et al, 2007), where at least part of the differences may be related to the characteristics of the L1 writing system (Martin, 2017). Importantly, studies of brain dynamics have shown varying patterns of EEG activity as a function of population type (i.e., L1 vs. L2), especially during the spelling of words that require non-phonological strategies (Weber et al, 2013). In this study, we compared children with (L1) and without (L2) exposure to Catalan, the language of instruction, outside school.…”
Section: Spelling Development In a Second Languagementioning
confidence: 99%